Indonesia’s Digital Diplomacy in Enchancing E-commerce Connectivity in ASEAN - Bangun, Siti Zainurrahmi Br; Andalia, Carolina Irene (LPPPIPublishing, 2026)
This study analyzes the crucial role of Digital Diplomacy implemented by Indonesia in the specific context of optimizing and enhancing connectivity in the e-commerce sector in the ASEAN region. In facing an increasingly digitalized industrial era, Digital Diplomacy not only serves as a new communication tool for state and non-state actors but also opens up significant economic opportunities for the national digital industry. Using a qualitative descriptive approach and case studies, this study in-depth explores how Indonesia's foreign policy utilizes digital technology and the internet to achieve economic goals. The research findings demonstrate that the strategic and effective implementation of digital technology is vital in building a positive image of Indonesia in the eyes of the international community. Indonesia is positioned as a country with high trade potential, supported by a large domestic market and rapid digital economic growth, even becoming the largest in ASEAN, with a value estimated to reach 330 billion by 2030. This positive image serves as a magnet to attract foreign investment on e-commerce platforms and effectively promote local products (MSMEs) to regional and global markets. Furthermore, this study highlights that rapid advances in information and communication technology (ICT) have revolutionized international trade. Social media networks formed through ICT have enabled more accessible cross-border e-commerce, despite challenges such as shipping costs and regulations. Indonesia's Digital Diplomacy Policy, which encompasses interactions between state and non-state actors in addressing international issues, seeks to leverage these developments to facilitate regional digital integration.